Strengthening Students' Ethics and Courtesy: The Implementation of Pancasila Values in An Urban Elementary School - Avelisa Belmont Situmeang; Widia Valentina Br Sihotang; Ignasya Rosari Omega Sinabariba; Larasinda Silitonga; Nazla Salsabila; Lukas Nister Fatrisyah Zega (PT. Mifandi Mandiri Digital, 2026)
Character education has become increasingly important in addressing issues related to students’ ethics and politeness in elementary schools. While many studies have examined Pancasila-based character education, limited research has specifically focused on its role in shaping students’ ethics and courtesy in a particular school context. This study aimed to analyze the implementation of Pancasila-based character values in shaping the ethical behavior and politeness of sixth-grade students at HKBP Maranatha Elementary School, Medan City.This study employed a quantitative survey method. The participants consisted of all 16 sixth-grade students, representing a school-based case study within a single class. Data were collected using a questionnaire containing 13 statements related to ethics and politeness and were analyzed using percentage analysis. The results showed that the implementation of Pancasila-based character values generally produced positive outcomes. Most students demonstrated tolerance, cooperation, and openness to criticism. A total of 81.25% of students often respected differences in religion, ethnicity, and family background, while 56.25% often helped classmates experiencing learning difficulties. Furthermore, 62.5% showed openness to criticism and suggestions. However, some aspects still require improvement, particularly self-control and empathy, as 62.5% of students admitted that they sometimes used harsh language while joking with friends. In conclusion, Pancasila-based character values play an important role in fostering students’ ethics and courtesy. Continuous character development is needed to strengthen empathy, self-control, and polite communication among students.